The archaeology of colonialism : intimate encounters and sexual effects - Voss, Barbara L.; Casella, Eleanor Conlin (New York : Cambridge University Press, 2012)
"This volume examines human sexuality as an intrinsic element in the interpretation of complex colonial societies"--Provided by publisher.
"This volume examines human sexuality as an intrinsic element in the interpretation of complex colonial societies. While archaeological studies of the historic past have explored the dynamics of European colonialism, such work has largely ignored broader issues of sexuality, embodiment, commemoration, reproduction, and sensuality. Recently, however, scholars have begun to recognize these issues as essential components of colonization and imperialism. This book explores a variety of case studies, revealing the multifaceted intersections of colonialism and sexuality. Incorporating work that ranges from Phoenician diasporic communities of the eighth century to Britain's nineteenth-century Australian penal colonies to the contemporary maroon community of Brazil, this volume changes the way we understand the relationship between sexuality and colonial history"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Sex -- Europe; Interpersonal relations -- Europe